Colonial Fantasies, Narrative Borders, and the Canadian North in the Works of Germany’s Colin Ross(1885-1945) - Pissowotzki, Nicole (Nordlit, 2009)
This paper argues that the Canadian North is a discursive construction, within which German colonial fantasies emerge. In particular, I argue that it is through bordering that colonial fantasies of German Lebensraum ("living space") in the Canadian North are brought into being. I further argue that the German biologist and geographer Friedrich Ratzel (1844-1904), with his view of the "organic state," provides the ideological framework for colonial fantasies in the travel writings of Colin Ross. I focus on the writer's colonial imagination and his perception of borders, and on how both relate to the Canadian North. I show that seemingly bare geographical information and demographical data, provided in Ross' travelogues, carry colonial fantasies of German spaces in the Canadian North. Those spaces are bordered by "shared histories" and "narrative boundaries," thus constructing a collective German colonial identity (cf. Eder 2006, 255-257).